(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The present article has as its central theme the group theater in Rio Grande do Norte. However, more than presenting the state of the art of the research we carry out, we seek to highlight how we do the research of the potiguar theater. This methodological option has two main reasons: 1. To unveil the knowledge and the research devices that we adopt in our group and projects; and 2. To expose the complexity of the task that we faced when we decided to translate the expression "teatro potiguar" in a way that more about the theater done in our state and country is known. Also, as a research collective, we sought to share some of the results of our investigations. This strategy of making evident some of the results of our ongoing research and the means we use for it reveals that we understand research as a collective act, whose ultimate goal is to create new worlds. In our case, with the broadening of knowledge about the theater being made in deep Brazil.